Sensitivity analysis from the blade angle regulation of the forced draught fans in an air-cooled steam condenser. (August 2017) - He, W.F.; Zhang, X.K.; Han, D.; Gao, L.
Highlights: Three blade angle regulations are first proposed. Fan performance at different blade angle regulations is calculated. Net power of the power plant is calculated. The optimal blade angle regulation strategy is obtained. Abstract: For enough cooling air flowing through the finned tube heat exchangers, the performance of the forced draught fans are always pivotal for the final characteristics of the air-cooled steam condenser (ACSC) as well as the power station. Hence, it is necessary to optimize the fan operation for a superior performance. In this paper, a previous numerical model is designated to execute the impact analysis from the blade angle regulation for forced draught fans with different positions on the performance of the air-cooled system at the prevailing wind angle of β = 22.5°. The simulation results indicate the fan volumetric effectiveness, heat transfer rate and the related equilibrium back pressure are influenced significantly once the fan blade angle is regulated. Compared with the design case, it is found that a maximum elevation of net power, 17.76 MW, is obtained for the fan array case when the wind speed is vm = 2 m·s −1 . Furthermore, it is found that the windward and peripheral case almost have a same effect to raise the net power of the power plant.